Patterns of Bioelectrical Brain Activity of Stroke Patients after Using Neurofeedback in the Rehabilitation Process - Trofimova, A; Silina, E; Dobrushina, O; Isaychev, S (KnE Life Sciences, 2018)
Background: Stroke patients develop the ability to perform higher levels of functional activity on basis of concentrated rehabilitative training which affects sensory, motor and cognitive functions. Objective: The main aim of our work was to show the usefullness of neurofeedback therapy in rehabilitation of stroke patients. Design: 27 stroke patients with severe disabilitis were included in the pilot study (men aged 32 to 68 years, mean age 52.4 ± 3.29 years, median 57 years). They all underwent complex study of brain bioelectrical activity EEG and 15 trainings of neurofeedback. Results: By the end of the rehabilitation (after 17 sessions) recollection of psychotrauma led to an increase in the power of the alpha rhythm in both left and right hemispheres. At the endpoint of the study differences in the power of the alpha rhythm in the left hemisphere were 1.47 times greater, and in the right hemisphere, 1.95 times greater than at the first visit. The regress of theta rhythm (1.25 times in the left, 1.11 times in the right hemisphere) decreased considerable, which affected the alpha / theta ratio - decreased 1.04 times in the left, 1.18 times in the right hemisphere, and also the coefficient (alpha + theta) / beta - decreased 1.17 times in the left and 1.21 times in the right. Differences in the saturation of blood vessels index at the last visit were 1.69 times greater than at the first visit. Neurophysiological changes correlated with an improvement in the emotional shpere. By the time of discharge, the indicators on the Beck depression scale decreased by 1.4 times, on the Spielberger-Khanin scale, situational anxiety decreased by 1.63 times, personal anxiety - by 1.4 times; regression of indicators in the hospital scale of anxiety and depression (HADS) was observed in 1.89 times. Conclusion: The data presented indicate that the use of the neurofeedback method leads to a reduction of anxiety-depressive disorders, which positively affects the usefulness of combine rehabilitation. Keywords: stroke, neurofeedback, electroencephalogram, alpha rhythm, rehabilitation.